THE EFFECT OF INFORMATION TRANSPARENCY AND DIGITAL ACCOUNTABILITY ON PUBLIC SERVICE SATISFACTION IN RANCAMANYAR VILLAGE - Afina Azzahra Almusthofa; Raden Imam Al Hafis (Yayasan Wayan Marwan Pulungan, 2026)
The acceleration of the Electronic-Based Government System (EBGS) demands a transformation toward transparent and accountable village governance. This study aims to analyze the influence of information transparency and digital accountability on public service satisfaction in Rancamanyar Village, Bandung Regency. Using a quantitative approach, this study relies on service users as the primary data source, collected through questionnaire distribution, and supported by secondary data in the form of a documentary study of the village’s official digital platform. Data analysis was conducted using descriptive and inferential statistics to test the significance of relationships between variables. The results indicate that information transparency and digital accountability simultaneously have a positive and significant effect on public service satisfaction in Rancamanyar Village. However, when examined separately, the documentary analysis and community perceptions reveal technical barriers, such as the lack of synchronization in data updates and the slow system response to resident complaints. These findings imply that the provision of digital infrastructure has not yet been fully matched by optimal bureaucratic responsiveness. This study recommends the need to strengthen standard operating procedures for periodic data updates and to improve the reliability of digital interaction channels in order to realize inclusive, user-centric public services